Pembentukan Biofilm Pseudomonas aeruginosa pada Beberapa Media Cair - Wahyudi, Didik; Sutariningsih Soetarto, Endang (Jurnal Farmasi (Journal of Pharmacy), 2021)
Pseudomonas aeruginosa is a Gram-negative rod-shaped bacterium that is an opportunistic pathogen that is the main cause of nosocomial infections and is able to form biofilms on growth media, biofilms often make the treatment of infectious diseases more difficult. There are several types of bacterial growth media, compositions and brands. The purpose of this study was to determine the ability of P. aeruginosa to form biofilms on several liquid culture media. P. aeruginosa was isolated from clinical samples from hospitals, the liquid media used were nutrient broth, lactose broth, brain-heart infusion (BHI), luria bertani broth, and tripticase soy broth. The biofilm formation test used the microtiter plate culture technique method, the ability to form biofilms was measured based on optical density using a microtiter plate reader at a wavelength of 570nm, with 0.1% crystal violet staining, after 24 hours incubation at 37oC, with 8 replications. The results showed that P. aeruginosa had the ability to form biofilms in nutrient broth 0.926±0.081, lactose broth 0.521±0.041, BHI 1.283±0.031, luria bertani 1,301±0.043, and trypticase soy broth media 1.563±0.032. The highest biofilm formation was in trypticase soy broth, and the lowest was in lactose broth, while in BHI and luria farming media the biofilm formation abilities were equivalent. The conclusion of this study is that P. aeruginosa has different abilities in forming biofilms when grown on different liquid media.